Burden of smoking on cause-specific mortality: application to the Nurses' Health Study. Issue 3 (25th May 2010) - Kenfield, Stacey A; Wei, Esther K; Rosner, Bernard A; Glynn, Robert J; Stampfer, Meir J; Colditz, Graham A
Abstract : Objective: The burden of smoking on six causes of death in women was evaluated using various novel modelling approaches. Design: A prospective US-based nationwide cohort study. Participants: 102 635 women in the Nurses' Health Study followed biennially from 1980 to 2004. Methods: The relation between cigarette smoking and cause-specific death was compared using baseline versus biennially updated smoking status. The authors used competing risk survival analysis to formally compare associations of smoking-related variables on risk of death as a result of coronary heart disease (CHD), cerebrovascular diseases, lung cancer, other respiratory diseases, other smoking-caused cancers and other causes. Results: The associations of current and former smoking were stronger with most cause-specific mortality when using updated information. The effect of each smoking-related variable differed significantly (ph <0.0001) across some causes of death. For example, risks increased by 5% for death due to other causes up to 37% for lung cancer death for a 5-year earlier age at initiation. Compared with continuing to smoke, former smokers with 5–10 years of cessation had a 25% reduction in risk of dying from other causes of death up to a 61% reduction in risk of dying from CHD and cerebrovascular diseases. Conclusions: The risks of smoking and the benefits from quitting are greater than previously reported, when utilising repeated measures of smoking data collected during follow-up, and vary by cause of death. Focused efforts to communicate the benefits of quitting to smokers and to prevent smoking initiation among children and youths should remain top public health priorities to reduce the worldwide mortality burden caused by smoking.